1969
DOI: 10.1084/jem.129.5.871
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Human Antibodies

Abstract: Antibodies to the blood group A and B substances in human sera are extraordinarily heterogeneous. Sera generally contain vG, ~,M, and ~A anfi-A or anti-B (1-6). Differences in properties of various sera by precipitation (4, 5), hemagglutination (4, 5, 7-9), hemolysis (8, 10, 11), complement fixation, (10-12) and fixation to skin (4, 13) have been found. To understand the extent of this heterogeneity it is essential to prepare and study blood group antibodies of the various immunoglobulin classes from single do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
1979
1979

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Ethyl chloroformate insolubilized (32,33) human anti-A serum Chris D2 (34) and D. biflorus (23) inselubilized on cyanogen bromide-activated Sepharose 2B (30,(35)(36)(37) were prepared as described earlier (26). Whole anti-A serum was acidified by adding 1.0 M sodium acetate-acetic acid buffer, pH 4.6, to a final concentration of 0.20 M (pH 4.9-5.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethyl chloroformate insolubilized (32,33) human anti-A serum Chris D2 (34) and D. biflorus (23) inselubilized on cyanogen bromide-activated Sepharose 2B (30,(35)(36)(37) were prepared as described earlier (26). Whole anti-A serum was acidified by adding 1.0 M sodium acetate-acetic acid buffer, pH 4.6, to a final concentration of 0.20 M (pH 4.9-5.0).…”
Section: Methodsmentioning
confidence: 99%
“…Such antibodies must have sites large enough to accommodate the whole determinant. The antibodies from Chris anti-A have been purified (34) according to size of the combining site by elution from PL-Hog A with DGalNAc followed by the ARL 0.52 pentasaccharide with the structure (5, 7) LFucal 2 DGaINAcal--*3DGaI~I--*4DGIcNAc~I--*6R.…”
Section: Competition For Binding Of Labeled Blood Groupmentioning
confidence: 99%
“…minant have been shown to be heterogeneous both with respect to size of combining sites (Kaplan and Kabat, 1966;Moreno and Kabat, 1969), heavy and light chains, and genetic markers (Yount et al, 1968;Dorner et al, 1969). Partial fractionation of antibodies with respect to size of combining site can be accomplished by specific elution with haptens representing the entire antigenic determinant or smaller parts of it (Schlossman Gelzer and Kabat, 1964a,b;Moreno and Kabat, 1969). Antibody heterogeneity seriously limits the study of sequence and the three-dimensional arrangements of amino acids in the combining region.…”
mentioning
confidence: 99%
“…Reduction of IgM anti-B to subunits was accompanied by a marked fall in equilibrium constant, suggesting that IgM anti-B is attached to red cells by at least two combining sites [3]. Moreno and Kabat [12] were unable to demonstrate binding of A hapten to IgM anti-A by equi librium dialysis, suggesting that the equilibrium constant of each binding site is extremely low. Moreno and Kabat [12], however, also experienced difficulty in obtaining IgM anti-A in eluates from columns of A glycoprotein and they suggested that this might be related to their high valency and hence to a higher binding constant than IgG anti-A for a multivalent glycoprotein antigen.…”
Section: Discussionmentioning
confidence: 99%